Burnout and resilience at work among health professionals serving in tertiary hospitals, in Ethiopia - Gelaw, Yared Mulu; Hanoch, Kashtan; Adini, Bruria (Frontiers in Public Health, 2023)
Background The quality of healthcare service is strongly affected by the health professionals’ levels of burnout and resilience at work (RaW). Developing resilience is a key component of medical professionalism. Although burnout and resilience are indicators used to assess the level of workplace hardship, there is a dearth of information in most developing countries, including Ethiopia. Objective To assess the levels of burnout and ‘resilience at work’ among health professionals who work in the surgical care departments in teaching Ethiopian hospitals. Methods A cross-sectional study design was applied among health professionals employed in surgical, gynecologic, and obstetric (Gyn/Obs) departments of two acute-care hospitals (n = 388). A structured self-administered English version questionnaire, consisting of validated scales to measure RaW and burnout, was used to collect the data;22 items of Maslach’s burnout inventory human service survey tool and 20 items of Win wood’s resilience at work’ measuring tool” was employed to assess the health professionals’ burnout level and Resilience at work, respectively. Linear logistics regression was employed for inferential statistical analysis to identify factors that predict RaW and burnout. Results Burnout syndrome was shown among 101 (26.0%) study participants. Furthermore, 205 (52.8%), 150 (38.7%), and 125 (32.2%) participants presented high emotional exhaustion, high depersonalization, and low personal accomplishment, respectively. Emotional exhaustion was predicted by the participants’ profession, the hope of promotion, professional recognition, and workload. Depersonalization was predicted by age, profession, and perceived workload of the participants. The predictors for personal accomplishment were profession, relationship at work, professional recognition, and having a managerial position in addition to clinical duty. The participants’ mean RaW score was 78.36 (Standard deviation ±17.78). A negative association was found between RaW and emotional exhaustion and depersonalization. In contrast, a positive association was identified between RaW and personal accomplishment. The type of profession and marital status were positive predictors of RaW. Conclusion A substantial amount of health professionals experience high burnout in one or more burnout dimensions. Level of RaW is more affected by burnout syndrome. Therefore, promoting activities that increase the level of professional RaW and recognition in their professional practice is needed to reduce job burnout. These findings are especially important concerning low socio-economic countries, as resilience is a vital component of the development of healthcare systems.